Alert - Patterson, James, 1947- (New York : Little Brown and Company, 2015)
New Yorkers aren't easily intimidated, but someone is doing their best to scare them. After two inexplicable high-tech attacks, the city is on edge. Detective Michael Bennett and FBI agent Emily Parker have to catch the shadowy criminals who claim responsibility.
"A Michael Bennett novel"-- Cover.
Includes an excerpt of James Patterson's "The Murder House" at the end of the book.
Keywords: Bennett, Michael (Fictitious character) -- Fiction; Suspense fiction; New York (N.Y.) -- Fiction